2022
DOI: 10.1111/pai.13783
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab may facilitate drug desensitization in patients failing standard protocols

Abstract: Omalizumab may facilitate drug desensitization in patients failing standard protocolsTo the Editor, Nephrotic syndrome (NS) is a common glomerular disorder in children, for which steroids are the first-line treatment. While most children with NS respond to steroid therapy, 20% of children are resistant to steroids. Some children with steroid-responsive NS develop a frequently relapsing or steroid-dependent course and experience significant side effects of steroid therapy. Alternative medications such as calcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…61 Karaaslan et al reported a case of successful omalizumab use in a pediatric patient with severe reactions to rituximab not responding to previous DDS protocols with 12,16, and 20 steps. 62 Therefore, the decision on whether to use premedication should (Continues) in Oncology should be maintained), the suspected HSR type and previous breakthrough symptoms. In the authors' view, the routine use of premedication should be avoided, particularly in suspected IgE-mediated reactions.…”
Section: Pretreatment Before Dds In Childrenmentioning
confidence: 99%
“…61 Karaaslan et al reported a case of successful omalizumab use in a pediatric patient with severe reactions to rituximab not responding to previous DDS protocols with 12,16, and 20 steps. 62 Therefore, the decision on whether to use premedication should (Continues) in Oncology should be maintained), the suspected HSR type and previous breakthrough symptoms. In the authors' view, the routine use of premedication should be avoided, particularly in suspected IgE-mediated reactions.…”
Section: Pretreatment Before Dds In Childrenmentioning
confidence: 99%
“…Moreover, premedication with omalizumab may facilitate RDD in specific phenotypes and allow the continuation of preferred treatment for those who have breakthrough reactions. 15 Drug allergy labels could impact negatively patient's quality of life and life expectancy. Endophenotyping is crucial to correctly diagnose and treat patients based on in vivo and in vitro tests.…”
Section: New Perspectives On Drug Allergy In Childrenmentioning
confidence: 99%
“…In this article, 269 RDDs were performed successfully, being 90% free of breakthrough reactions. Moreover, premedication with omalizumab may facilitate RDD in specific phenotypes and allow the continuation of preferred treatment for those who have breakthrough reactions 15 …”
mentioning
confidence: 99%
“…The patient remained asymptomatic while also receiving mycophenolate and only 2 mg of prednisone daily. In a patient receiving chemotherapy with FOLFIRINOX (folinic acid, 5-fluorouracil, irinotecan, and oxaliplatin) who had an episode of anaphylaxis during third desensitization, there were no further episodes of anaphylaxis during 13 additional desensitizations after starting the patient on omalizumab Omalizumab has even been used successfully for desensitization to rituximab in children [85].…”
Section: Desensitization Using Biologicsmentioning
confidence: 99%